Serat Bambu Petung (Dendrocalamus asper) Teralkalisasi sebagai Penguat Komposit Polimer - Gunawan Refiadi; Novan Bayu; Hermawan Judawisastra; Mardiyati Mardiyati (JURNAL SELULOSA, 2018)
The alkalized of petung bamboo fiber (Dendrocalamus asper) as reinforcement of polymer compositeAbstractPetung bamboo (Dendrocalamus asper) has good fiber characteristic and it has potential to substitute glass fiber as reinforcement in polymeric composite. However, like other natural based materials, bamboo fiber has a high variability in mechanical properties and inherently hygroscopic characteristic. Therefore it is required to optimize the petung bamboo qualities. The fiber optimization was carried out by alkalization process using NaOH solution with varying concentration of 0, 3, 5, and 10% v/v. Bamboo fiber processed in chemomechanical was used in this investigation. Characterization of density, mechanical and chemicals was conducted by pycnometry method, tensile strength testing, Fourier Transform Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The data variability was analyzed by Weibull distribution. Result indicates that the optimum condition of alkalization process of bamboo fiber using NaOH solution of 5% v/v which has fiber diameter of 175.098 ± 58.017 mm, tensile strength of 384 MPa, and characteristics strength of 390.5 MPa.Keywords: petung bamboo; alkalization; characteristics AbstractBambu petung memiliki karakteristik serat yang baik sehingga berpotensi sebagai pengganti serat gelas untuk penguat komposit polimer. Namun, seperti umumnya serat alam, serat bambu memiliki variabilitas sifat mekanis tinggi dan sifat higroskopik yang inheren. Oleh karena itu diperlukan upaya optimalisasi kinerja serat bambu petung. Optimalisasi kinerja serat dilakukan melalui proses alkalisasi dengan variasi larutan NaOH pada konsentrasi 0, 3, 5, dan 10% v/v. Serat bambu hasil dari proses kimia-mekanik digunakan dalam penelitian ini. Karakterisasi densitas, sifat mekanik, dan sifat kimia serat masing-masing dilakukan dengan metode piknometri, uji tarik, Fourier Transform Spectroscopy (FTIR), Scanning Electron Microscopy (SEM). Analisis variabilitas data menggunakan distribusi Weibull. Hasil menunjukkan bahwa kondisi optimum alkalisasi serat bambu petung yaitu menggunakan larutan NaOH 5% v/v yang menghasilkan serat berdiameter 175,098 ± 58,017 mm, kekuatan Tarik 384 MPa, dan kekuatan karakteristik 390,5 MPa.Kata kunci: bambu petung; alkalisasi; karakteristik